Woman critiqued : translated essays on Japanese women's writing - Copeland, Rebecca L., 1956- (University of Hawai'i Press, 2006)
'Women Critiqued' offers English-language readers access to some of the salient critiques that have been directed at women writers, on the one hand, and reactions to these by women writers, on the other.
Keywords: Japanese literature -- Women authors -- History and criticism.; Japanese literature -- 20th century -- History and criticism.; Women authors, Japanese -- 20th century.; Japanese literature -- 1868- -- History and criticism.; Écrits de femmes japonais -- Histoire et critique; Littérature japonaise -- 20e siècle -- Histoire et critique.; Littérature japonaise -- 1868- -- Histoire et critique.; Écrivaines japonaises -- 20e siècle.; LITERARY CRITICISM -- Asian -- General.; LITERARY CRITICISM -- Asian -- Japanese.; Japanese literature; Japanese literature -- Women authors; Women authors, Japanese; Literaturtheorie; Schriftstellerin; Japan; Japanisch.; Since 1868; Criticism, interpretation, etc.